IMPERATOR CONTRA PRAEDONES UWAGI O „NIEKONSTYTUCYJNOŚCI” LEX GABINIA - Tarwacka, Anna (Zeszyty Prawnicze, 2017)
Imperator contra praedones Some Remarks on the Illegality of the lex Gabinia Summary In 67 BC Aulus Gabinius, a tribunus plebis, proposed a law appointing an imperator to deal with the pirates of the Mediterranean area. The law was passed as lex Gabinia de uno imperatore contra praedones constituendo and the senate was asked to choose the right candidate. The only possible choice was Gnaeus Pompeius Magnus, the most talented and famous general of the time. The senators opposed so violently that Gabinius was almost killed. Thus, another assembly was called which appointed Pompey to the task. His campaign against the pirates was amazingly fast and successful. There are several reasons for treating this case as a deviation from the republican constitution. Firstly, the imperium was given for a period of three years which was unusually long time for an extraordinary command. Secondly, the general was given power on the whole Mediterranean area, equal to this of the provincial governors. Thirdly, he could choose his own legati which was a case unknown to the republican system. Moreover, it was the first time when an extraordinary command was given by the concilia plebis regardless the senatorial opposition. The case of lex Gabinia was one of Pompey’s numerous victories over the republic. Notwithstanding, he managed to persuade everyone to picture himself as a hero and defender o f the republic.